A review on shellfish polysaccharides: Extraction, characterization and amelioration of metabolic syndrome - Xiang, Xingwei; Jiang, Qihong; Yang, Hongshun; Zhou, Xuxia; Chen, Yufeng; Chen, Hui; Liu, Shulai; Chen, Lin (Frontiers in Nutrition, 2022)
Shellfish are diverse, widely distributed organisms that are a rich source of biological resources. Polysaccharides are the main components in shellfish, hence a great deal of attention has been directed at isolation and characterization of shellfish polysaccharides because of their numerous health benefits. Differences in shellfish species, habits, and environment result in the diversity of the structure and composition of polysaccharides. Thus, shellfish polysaccharides possess special biological activities. Studies have shown that shellfish polysaccharides exert biological activities, including antioxidant, antitumor, immune-regulation, hypolipidemic, antihypertensive, and antihyperglycemic effects, and are widely used in cosmetics, health products, and medicine. This review spotlights the extraction and purification methods of shellfish polysaccharides; discusses the regulatory mechanism of shellfish polysaccharides on hyperlipidemia, hypertension, and hyperglycemia caused by lipid metabolism disorders; and summarizes its alleviation of lipid metabolism-related diseases. This review provides a reference for the in-depth development and utilization of shellfish polysaccharides as a functional food to regulate lipid metabolism-related diseases.